Study of chronic toxicity of narrow-leaved lavender extracts: influence on functional status and laboratory indicators of rats - Bogatyrova , Olena; Naboka , Olga (Annals of Mechnikov’s Institute, 2024)
Introduction. Despite the widespread use of chemotherapeutic drugs, medicinal plants continue to maintain the scientific interest of today’s pharmacologists. In order to saturate the domestic pharmaceutical sector with affordable phytopreparations of a wide spectrum of action, scientists of the National Pharmaceutical University (postgraduate student Gurina V.O. under the supervision of Doctor of Pharmaceutical Sciences, Professor Georgiyants V.A.) obtained extracts of narrow-leaved lavender containing biologically active substances: terpenoids (linalool, linalyl acetate and traces of 1,8-cineole), flavonoids (hyperoside, isoquercitrin) and hydroxycinnamic acids (rosmarinic, chlorogenic). As a result of experimental microbiological tests, it was established that the herb of narrow-leaved lavender of Ukrainian origin is a promising and affordable source of potential antimicrobial active pharmaceutical ingredients. Also, based on the results of studying the acute toxicity of narrow-leaved lavender extracts when administered intragastrically to white mice, conclusions were drawn that allowed the studied test samples to be classified as class V of practically non-toxic substances (LD50>5000 mg/kg). The aim of the work. Experimental study of the toxicological properties of extracts of L. angustifolia (chronic toxicity) to substantiate the safety of use in clinical practice. Materials and methods. The objects of the study were experimental test samples: No. 1 - extract of narrow-leaved lavender obtained by extraction with purified water; No. 2 - extract of narrow-leaved lavender obtained by extraction with a water-ethanol solution (40% ethanol); No. 3 - extract of narrow-leaved lavender obtained by extraction with a water-ethanol solution (70% ethanol). Test samples of narrow-leaved lavender were used at a dose of 100 mg/kg, which corresponds to 1/50 of the LD50 of the experimental agents, which was determined at the previous stage of the study. Chronic toxicity studies of narrow-leaved lavender extracts were conducted on 48 white non-linear rats of both sexes with an initial weight of 170-190 g with daily intragastric administration for 90 days. In the collected urine, general properties (colour, transparency, pH, density), total protein content (by reaction with sulfosalicylic acid), glucose content (by glucose oxidase method) and urinary sediment were determined. Then, a complete laboratory blood test was performed using general scientific haematological methods and the following were determined: haemoglobin and erythrocyte content, colour index, leukocyte content, leukocyte formula, and erythrocyte sedimentation rate. Creatinine content (by reaction with picric acid) in blood and urine was determined. Endogenous creatinine clearance was calculated to assess the glomerular filtration rate. In the blood serum of rats, the urea content (diacetylmonooxime method), total protein (biuret method), glucose content (glucose oxidase method), ALT and AST activity (Reitman-Frankel method), bilirubin content (Jendrassik-Grof method), cholesterol content (modified Liebermann-Burchard method) were determined. The significance of differences between samples was assessed using the Kruskal-Wallis method and the Mann-Whitney test in comparison with the intact control group. Results and discussion. According to the results of experimental studies, it was found that intragastric administration of lavender test samples in selected doses throughout the entire observation period did not have a significant negative effect on the general condition, condition of the skin and mucous membranes and behaviour of rats. During the experiment, no case of animal mortality was registered. All indicators of the body weight of rats were within the physiological norm for this age group. On the 45th and 90th day of the study, no statistically significant effect of the extracts was registered relative to the intact group on the indicators of spontaneous daily diuresis, specific gravity and pH of the urine of animals. The use of narrow-leaved lavender test samples did not have a significant effect on the indicators of the level of glucosuria in rats of all experimental groups, while this indicator was not determined by generally accepted methods of quantitative and qualitative analysis, which is within the physiological norm. During the analysis of the urinary sediment of animals receiving narrow-leaved lavender extracts, no signs of urinary syndrome and pathophysiological changes in the ratios of formed elements were detected. The content of erythrocytes, leukocytes, epithelium, and cylinders was within the physiological norm, and at the level of intact animals, it was 0-3 in the field of view. With prolonged use of narrow-leaved lavender test samples, no statistically significant effect was observed on nitrogen metabolism and biochemical blood parameters in animals. Fluctuations in blood urea and creatinine were within the physiological norm. All studied parameters: glucose, total protein, cholesterol, bilirubin, AlAT and AsAT activity in the intact and experimental groups are within the range of normal values ​​for rats and do not exceed the physiological norm. This indicates that lavender test samples in the studied doses with intragastric administration do not affect the parameters characterizing the functional state of the liver and kidneys of rats. During the study, no toxic effect was recorded on the parameters of peripheral blood of rats. In the leukocyte formula of rats of the experimental groups under the influence of chronic use of narrow-leaved lavender test samples, the percentage ratio of different forms of leukocytes also corresponded to intact animals and did not differ from the normal values. The only exception can be considered to be the increase in the content of rod-shaped neutrophils under the influence of test sample No. 2 as of day 90 of the study, which probably exceeds the intact level but, despite this, is within the physiological norm for rats. Conclusions. With chronic (90 days) intragastric administration, test samples of L. angustifolia at a dose of 100 mg/kg do not cause death in rats. It has been established that under conditions of chronic use, test samples of narrow-leaved lavender do not have a toxic effect on the general condition, behaviour and dynamics of body weight, do not cause significant differences in laboratory test parameters of urine and blood, and practically do not affect the functional state of the urinary and hepatobiliary systems of animals.